ASUPAN ENERGI, ASUPAN PROTEIN, AKTIFITAS FISIK DAN STATUS GIZI PADA REMAJA PUTRI PUTRI DI PONDOK PESANTREN (Politeknik Kesehatan Kemenkes Bandung, 2022)
An imbalance in nutrient adequacy levels can cause nutritional problems, both undernutrition, and overnutrition. Adolescent energy needs are influenced by activity, basal metabolism, and the increased need to support accelerated growth and development during adolescence, while protein requirements in adolescents are determined by the amount of protein to support lean body mass and the amount of protein needed to increase lean body mass during accelerated growth. . This research was conducted with a cross-sectional design, a minimum sample of 44 people, taken by simple random sampling. The data collected included data on energy intake, protein intake, using 24-hour recall, physical activity using a 24-hour record of physical activity, and nutritional status obtained using anthropometric measurements and weighing. The study found that 81.8% had less energy intake, 90.9% had less protein intake and 45.5% of female students had light physical activity, 54.5% had moderate activity and 13.6% of female students had poor nutritional status, 65, 9% had normal nutritional status, 15.9% overweight and 4.5% obese. The proportion of samples with less energy intake had a poor nutritional status of 16.7% or higher than good intake. The proportion of samples with low protein intake had a 15% or higher nutritional status than those with good protein intake.